Budget Preparation Training to Increase Operational Profit of UMKM Srikandi Bakti Real Village Tanjung Rejo Percut Sei Tuan Deli Serdang - Herlin Munthe; Khasrad; Rafida Khairani; Purnama Yanti Purba; Kristi Endah Ndilosa Ginting; Rudiyanto (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The main problem faced by UMKM Sri Kandi is not based on science and technology. Indicators of problems that occur are financial management that has not been based on good planning/budgeting. Most members of Srikandi Bakti Nyata run a business with information that is not well organized. The purpose of this PKM is to help UMKM actors in preparing budgets better, so they can predict future sales and costs. The implementation of community service activities uses the method action research. The form of the activity carried out was in the form of training socialization in compiling a budget to be able to increase operating profit at the Srikandi Bakti Nyata UMKM in the village of Tanjung Rejo Percut Sei Tuan Deli Serdang. UMKM budget training activities can also improve the financial performance of the Srikandi group so that income also increases.